Efektivitas Penagihan Pajak Aktif dengan Surat Teguran, Surat Paksa, dan Surat Pelaksanaan Melakukan Penyitaan terhadap Penerimaan Pajak Penghasilan pada KPP Pratama Rantau Prapat - Rizah Ummammy; Arnida Wahyuni Lubis (VISA: Journal of Vision and Ideas, 2023)
The main and largest source of income in Indonesia today is from taxes. Taxes are used to finance government expenditures needed to increase national development and improve the welfare of citizens. In order to achieve the effectiveness and efficiency of tax collection, DGT continues to improve law enforcement through passive and active tax collection activities. This study aims to determine the effectiveness of active tax collection with a letter of reprimand, a letter of compulsion, and a letter of execution to confiscate income tax receipts at KPP Pratama Rantau Prapat. The analytical method used in this study is descriptive analysis to provide an overview of whether tax collection with a letter of reprimand, a letter of compulsion, and a letter of execution for confiscation has been effective or not. The research data obtained were analyzed using descriptive statistics in the form of descriptive ratios. The test results show that tax collection with letters of reprimand and letters of compulsion in 2020 and 2021 is classified as ineffective. Therefore, the Head of KPP Pratama Rantau Prapat must make various efforts both internally and externally to improve the efficiency of tax collection in his working area. Keywords: Effectiveness, Tax Collection, Warrant, Forced Letter, Warrant Doing Foreclosure